HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DAN KOORDINASI MATA DAN TANGAN DENGAN AKURASI SERVIS ATAS TIM BOLAVOLI PUTRA SMK MUHAMMADIYAH 02 PEKANBARU - Harry Kurniawan; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on field observations, it is clear that during practice and inter-school matches, it is seen from the ball blow when the top serve of the ball is often out of the field and sometimes stalls on the net or hit the net, some even do not get to the field opponent. In accordance with the background problems and problem formulation, this study aims to determine the relationship of muscle strength of the arms and shoulders and eye and hand coordination with the accuracy of service over the men's bolavoli team SMK Muhammadiyah 02 Pekanbaru. The population in this study is the men's bolavoli team SMK Muhammadiyah 02 Pekanbaru registered or active follow the training which amounted to 12 people. Given the total population of less than 100 people, then the entire population is sampled (total sampling) as many as 12 people. Instruments in this research are dynamometer expander, throw capture ball to wall and service accuracy. The data obtained in the analysis by using product moment correlation. Based on the results of research that has been authors described in the previous chapter, it can be concluded that the results obtained muscle strength of the arms and shoulders have no relationship with the accuracy of service on the team bolavoli son SMK Muhammadiyah 02 Pekanbaru. From the results obtained eye and hand coordination has no relationship with the accuracy of service on the team bolavoli son SMK Muhammadiyah 02 Pekanbaru. There is no relationship simultaneously between arm muscle strength and shoulder and eye and hand coordination on service accuracy on the men's bolavoli team SMK Muhammadiyah 02 Pekanbaru.Keywords; Muscle Arm and Shoulder Strength, Eye and Hand Coordination, Service Accuracy